Product Differentiated Learning Based on Local Wisdom in Biotechnology to Improve Science Literacy Skills - Iis Widayati (Science Center Group, 2024)
Background: The integration of local wisdom into biotechnology instruction has gained increasing attention as a contextual strategy to enhance students’ science literacy. However, its implementation in Indonesian science classrooms remains limited, and innovative differentiated approaches are still underexplored. Objective: This study aimed to analyze the effectiveness of product-differentiated learning based on local wisdom in biotechnology in improving junior high school students’ science literacy skills. Methods: A quantitative quasi-experimental design with a non-equivalent control group was employed. Participants were Grade IX students selected through purposive sampling and assigned to either an experimental group receiving product-differentiated learning integrated with local wisdom or a control group receiving conventional instruction. The intervention involved specially designed modules incorporating local cultural contexts, practical activities, group discussions, and product-based projects. Science literacy was measured using pre- and post-tests assessing conceptual understanding, analytical ability, and application skills. Data were analyzed using independent samples t-tests. Results: The findings revealed a statistically significant improvement in science literacy skills among students in the experimental group compared to the control group (p < 0.05). Students exposed to local wisdom-based differentiated learning demonstrated higher engagement, stronger conceptual comprehension, and improved ability to apply biotechnology concepts in real-life contexts. Reflective journals further indicated increased motivation and positive attitudes toward science learning. Conclusion: Product-differentiated learning grounded in local wisdom significantly enhances students’ science literacy in biotechnology. Integrating culturally relevant contexts into science instruction provides a meaningful learning experience and supports the development of higher-order thinking skills. This approach offers practical implications for curriculum development and contextual science education reform.